1928
DOI: 10.1037/h0070936
|View full text |Cite
|
Sign up to set email alerts
|

The effect of electric shock as punishment for errors in human maze-learning.

Abstract: It was not thought necessary to present the directions here. They were similar to the directions ordinarily employed in maze experiments with human adults..

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1930
1930
1982
1982

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 5 publications
2
16
0
Order By: Relevance
“…The subjects were, no doubt, highly motivated by the experimental situation, and the shock may have added but little to this already-pre sent desire to do well. However, the addition of a shock to a maze-learning situation does increase the speed of learning (4,5,8,9,10,11). We may, then, extend our discussion as follows.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The subjects were, no doubt, highly motivated by the experimental situation, and the shock may have added but little to this already-pre sent desire to do well. However, the addition of a shock to a maze-learning situation does increase the speed of learning (4,5,8,9,10,11). We may, then, extend our discussion as follows.…”
Section: Discussionmentioning
confidence: 86%
“…Table 1 gives the complete error scores for all S's of the U. C. L. A. experiment, and Table 2 shows the same data for the Alabama Group. It will be recalled from Figure 1 that Group I in each experiment was shocked in true Paths 1,2,4,8,and 9,and in Blinds 3,5,6,7,and 10. For Group II this situation was exactly reversed.…”
Section: B Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the'' ordinary curves" (figs. 3,5,6,7,8,9), each point plotted represents the average daily score in errors or time per trial. In the case of error curves, this average was found by dividing the total daily error score by the total number of rats in the group.…”
Section: Methods Of Drawing Error and Time Curves (A)mentioning
confidence: 99%
“…In human learning of a stylus maze, Bunch (5) found that electric shock given for errors decreased the number of errors. Rexroad (6) got somewhat ambiguous results in a human multiple choice reaction experiment in which electric shock was admin-Lstered for errors.…”
Section: Introductionmentioning
confidence: 99%